2022
DOI: 10.1142/s1013702522500056
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of tensioning and sliding neural mobilization on peripheral and autonomic nervous system function: A randomized controlled trial

Abstract: Background: Although different types of neural mobilization (NM) exercises induce different amounts of longitudinal nerve excursion and strain, the question whether the increased longitudinal stress and nerve excursion from sliding or tensioning intervention may subtly affect the neural functions has not been answered yet. Objective: To compare the effects of tensioning NM versus sliding NM of the median nerve on peripheral and autonomic nervous system function. Methods: In this randomized controlled trial, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Morsi et al, (2021),Alshami et al, (2021) which was consistent with the literature as both slider and tensioner NM exercises are found to reduce sciatica pain and improve ROM(Alharmoodi et al, 2022;Papacharalambous et al, 2022). With the tensioner technique, NM is obtained by moving one or several joints to elongate the nerve bed, forcing the nerve to slide relative to its surrounding structures.Biomechanical studies have demonstrated that a joint movement that elongates the nerve bed can increase the strain (the ratio of elongation to the original length) in the nervous system, and this cumulative increase in strain occurs if several joint movements are combined.Alternatively, in the slider technique, at least two joints are moved simultaneously in such a manner that the movement in one joint counterbalances the increase in nerve strain caused by the other movement.…”
mentioning
confidence: 56%
“…Morsi et al, (2021),Alshami et al, (2021) which was consistent with the literature as both slider and tensioner NM exercises are found to reduce sciatica pain and improve ROM(Alharmoodi et al, 2022;Papacharalambous et al, 2022). With the tensioner technique, NM is obtained by moving one or several joints to elongate the nerve bed, forcing the nerve to slide relative to its surrounding structures.Biomechanical studies have demonstrated that a joint movement that elongates the nerve bed can increase the strain (the ratio of elongation to the original length) in the nervous system, and this cumulative increase in strain occurs if several joint movements are combined.Alternatively, in the slider technique, at least two joints are moved simultaneously in such a manner that the movement in one joint counterbalances the increase in nerve strain caused by the other movement.…”
mentioning
confidence: 56%
“…A significant effect favouring tensioning techniques but not sliding techniques conflicts with the findings of a recent study that compared the neurophysiological responses of sliding and tensioning and reported the tensioning technique to have adverse effects on the nerves, such as decreased amplitude of the dermatomal somatosensory evoked potential. 90 In addition, one of the studies included in this review, but not in the meta-analysis, compared the sliding against tensioning neural mobilisation and reported significant results favouring the sliding technique for both pain intensity and functional status. 69 Another trial, not included in this review because it included participants with neuropathic pain, found no differences between the two techniques for pain intensity.…”
Section: Discussionmentioning
confidence: 98%
“…The tensioning technique increase the potential for nerve adverse reactions [29]. Our decision was further supported by a desire to gather comprehensive data on the effects of neural mobilization on peripheral nervous system function while mitigating the potential for adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Dermatomal somatosensory evoked potentials (DSSEPs) were the primary outcome measure employed to assess the impact of the treatment. The higher the DSSEPs amplitude the better the implication it has for the neural effect [29].…”
Section: Outcome Measuresmentioning
confidence: 99%